Implementasi Kegiatan Keagamaan dan Budaya Literasi Pada Siswa di Madrasah Tsanawiyah Berbasis Pesantren - Maulidina, Insani Fitri; Cahyono, Guntur (Indonesian Journal of Muhammadiyah Studies (IJMUS), 2023)
The aim of this research is to determine the implementation of religious activities and the implementation of literacy culture among students at MTs Al-Mu'min Muhammadiyah Tembarak, Temanggung Regency. This type of research is field research, and the approach used is descriptive qualitative. Data sources in this research include primary sources, namely the results of interviews with school principals, curriculum cadets, teachers and students. Secondary sources in this research are school profiles, photos of activities related to religious activities and literacy culture, and photos of awards for the school. Data collection was carried out by means of interviews, observation and documentation. The results of the research show that: 1) The implementation of religious activities for students at MTs Al-Mu'min Muhammadiyah Tembarak includes fardhu prayers in congregation, reading prayers, tahsin, tahfidzul Qur'an, memorizing muroja'ah, imla', qiro 'atul pole, dhuha prayers in congregation, kultum, PDL (Field Da'wah Training), murokaz, morning mufrodat and mahfudzot, muhawarah/conversation, muhadharah, PHBI (Islamic Holiday Commemoration), and religious social service; 2) Implementation of literacy culture among students at MTs Al-Mu'min Muhammadiyah Tembarak, Temaggung Regency, including the Cerah Tsamuha bulletin, class and madrasa wall boards, work studies, literacy camps, publishing student anthology books, book reviews, research, and use of digital media.